2017
DOI: 10.1088/1361-6641/aa7eed
|View full text |Cite
|
Sign up to set email alerts
|

The effect of reactive ion etch (RIE) process conditions on ReRAM device performance

Abstract: The recent surge of research on resistive random access memory (ReRAM) devices has resulted in a wealth of different materials and fabrication approaches. In this work, we describe the performance implications of utilizing a reactive ion etch (RIE) based process to fabricate HfO 2 based ReRAM devices, versus a more unconventional shadow mask fabrication approach. The work is the result of an effort to increase device yield and reduce individual device size. Our results show that choice of RIE etch gas (SF 6 ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The calculation of defect density has been reported in many previous researches. [27][28][29][30] In this work, we assume that some defects that cause dielectric breakdown exist in the pattern edge of the MTJ samples. Then the defect density can be calculated with the following equation…”
Section: Discussionmentioning
confidence: 99%
“…The calculation of defect density has been reported in many previous researches. [27][28][29][30] In this work, we assume that some defects that cause dielectric breakdown exist in the pattern edge of the MTJ samples. Then the defect density can be calculated with the following equation…”
Section: Discussionmentioning
confidence: 99%
“…The etching step may lead to material redeposition along the device's sidewalls. This material can form a leakage path next to the VCM-based memristive device reducing the resistance and the forming voltage and increasing the device's variability [1,1]. After manufacturing the TE, the memristor is pacified, which means that the device is isolated from the surroundings and the TE is connected to the metal layers.…”
Section: Manufacturing Process and Possible Defectsmentioning
confidence: 99%
“…Various studies for the stable controllability of metal oxide-based RRAM, with TiO 2 [7,9], Ta 2 O 5 [5,10], and HfO 2 [4,11] being the most popular [9], have been conducted. Improvements in resistance variability and controllability have been achieved using pulse modulation [5], structural modification [10,11], fabrication [12], and interfacial analysis, [8,9]. Furthermore, it has been suggested that bi-layered RRAM with a certain combination of metal oxides produces remarkably reliable and gradual multistate resistance change [9,13].…”
Section: Introductionmentioning
confidence: 99%